DEVELOPMENT OF HYPERLINK-BASED LEARNING MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES IN ATOM MATERIALS - Vina Anastasya Hara Tambun; Marini Damanik (Chimica Didactica Acta)
The development of technology directly requires the world of education to adjust these developments in improving the quality of education to create quality human resources. So that the world of education must be able to utilize technology to create more interesting, comprehensive, and interactive multimedia-based learning media. The purpose of this research and development is to describe the preparation steps and feasibility (validity) of Hyperlink-based PowerPoint learning media to improve student learning outcomes through learning media using the Hyperlink-based PowerPoint learning model which was developed in chemistry learning the development of atomic theory. This research and development produced PowerPoint learning media based on Hyperlink on atomic theory development material which has been declared feasible with the aim of learning media that are interesting and concise but complete for use by students and teachers and improve student learning outcomes. Validity was fulfilled based on the assessment of the validator by material experts and media experts with a feasibility level for media eligibility of 91.3% and material eligibility of 89% so that it is in the very feasible category for media and material. The results of the questionnaire to obtain student responses to the developed Android-based learning media were 80.6%. The results of increasing the value in chemistry learning on the material for the development of atomic theory using PowerPoint learning media based on Hyperlink includes 92.12% of the average student score and is in the very good category which shows that PowerPoint learning media based on Hyperlink on atomic theory development material is suitable for use as a medium learning and to improve student learning outcomes.